THE CONSTRUCTION OF MUSLIM IDENTIY POST SPECIAL AUTONOMY: The Study of Majelis Muslim Papua Existence - Rumbaru; Hasse (IAIN Tulungagung, 2018)
This paper is going to explore the issue about the construction of Muslim identity in Papua. There are many challenges faced by Muslim particularly on identity in Papua. The existence of Muslim placed in Majelis MuslimPapua provides strongly the collectives of Muslim. The well-beings give in the changes of relation patterns among communities in Papua. Muslim is being seen as the one that can change Papua including demographics, politics, and economics. This paper has been done in Jayapura city since 2016. The data are collected through observation, in-depth interview, and literature review. There are three findings in this study. The first finding is that Majelis MuslimPapua is not only the communication media for Muslim people but also the fights media for Muslim of Papua after the special autonomy prevailed. Majelis Muslim Papua is a response of the relationship dynamic of all people in Papua especially in Jayapura which is so dynamic. The second is Muslim of Papua is being taken as the power to change in Papua especially on the citizens’ composition or demography according to the religions. Immigrants who come in Papua are strongly working on the changes in cultures and structures which are built before. The last finding is the existence of Muslim of Papuaestablishes multiculturalism and admits each other in the lives of Papua that is more open.